Computational and Molecular Studies Related to Multidrug Resistant Microorganisms Isolated from Clinical Sample - Vaishnavi1, Dr. V. Prabakaran2, M. Subhathra1, M.Vigneeswaran1, R. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">To evaluate the bacteria belonging to genus Pseudomonas sp, Staphylococcus sp E.coli, Klebsiella sp obtained from various clinical Samples (urine, blood, pus, and catheter) obtained from diagnostics labs and hospitals of Madurai were screened for their multi drug resistance using standard antibiotics such as Ampicillin trihydrate (A), Chloramphenicol (C), Gentamycin (G), Tetracycline hydrochloride (T). Ampicillin (A), Ceftazidime(CA), Amikacin(AK), Levofloxacin(LE), Cefuroxime(CU), Co-trimoxazole(CO),Â Â Nalidixic acid (NA), Streptomycin (S), antibiotics with the National committee for clinical laboratory standard (NCCLS) new interpretive criteria. The isolates that were showing multi drug- resistance were further evaluated for polymerase chain reaction PCR as a gold standard method to evaluate the resistant gene by the method, Muller Hinton agar (disc diffusion method).Â The results showing Multidrug resistant gene that has as vehicles for transmission of genetic information involved in spread of antibiotic resistance into various species, and to analyze the gene possessing the features of MDR using PCR amplification of suspected genes associated with resistance production.